Ir/Al multilayer Gates for High Temperature Operated AlGaN/GaN HEMTs. Issue 12 (29th September 2017) - Lalinský, Tibor; Vanko, Gabriel; Dobročka, Edmund; Osvald, Jozef; Babchenko, Oleg; Dzuba, Jaroslav; Veselý, Marián; Vančo, L'ubomír; Vogrinčič, Peter; Vincze, Andrej
Abstract : The fabrication and characterization of the sequentially evaporated Ir/Al multilayer gates of AlGaN/GaN circular high electron mobility transistors formed by high temperature oxidation is reported. Annealing at temperature of 800 °C, for 60 s in O2 ambient makes possible to form a sharp gate interface with a high Schottky barrier height at RT ( φ b  = 1.2 eV). It is also shown that high temperature oxidation can be an effective approach in reducing of both the gate and drain leakage currents of high electron mobility transistors (more than six orders). A comprehensive microstructural, electrical, and electro‐thermal characterization of the Ir/Al gates is carried out to study the thermal stability of the gate interface and high temperature performance of the devices. Stable operation of the devices with multilayer Ir/Al gates in the temperature range up to 500 °C is demonstrated. Here, it is proposed that the thermal stability of the interface is controlled by the formed aluminum oxide interfacial layer. Finally, perfectly clear pinch‐off characteristics and thermally induced threshold voltage ( V th ) instability as low as −0.58 mV °C −1 are achieved. Abstract : In this paper, AlGaN/GaN circular high electron mobility transistors (C‐HEMTs) capable to operate at elevated temperatures are presented . To withstand high temperature operation, a new design concept of the Schottky gate electrode is introduced. It consists of Ir/Al multilayers formed by high temperature oxidation (annealing in O2 at T  = 800  o C for 60 s). It provides (a) high thermally stable Schottky barrier height, (b) low leakage currents, and (c) gate to be free of Au.